AKUNTABILITAS DAN TRANSPARANSI PELAPORAN KEUANGAN PEMERINTAH DAERAH SERTA POTENSI WHISTLEBLOWING ATAS PENYALAHGUNAAN DANA - Anggi Saputra; Intiyas Utami; Ika Kristianti (Fakultas Ekonomi, Universitas Negeri Jakarta, 2018)
The high level of corruption in the Indonesian government sector makes good governance difficult to achieve. Accountability and transparency is a must in the effort to realize good governance. The efforts to reduce the level of corruption in Indonesia is the awareness of civil servants to disclose the fraud in the workplace agencies. This research uses qualitative methods with the aim to describe the implementation of accountability and transparency of local government financial reporting as well as identify potential whistleblowing for misuse of funds. This research uses primary data in the form of in-depth interviews with informants and secondary data in the form of financial statements of Salatiga local government that has been audited by BPK. The resource persons in this research are civil servants domiciled in Salatiga City and work in SKPD Salatiga City in the finance department of each SKPD. The results of this research indicate that Salatiga City Government has been accountable and transparent in local government financial reporting as well as there is no potential whistleblowing for misuse of funds. The results of this research can be used as an evaluation material for government agencies to establish a good whistleblowing mechanism so that civil servants working in government agencies are more willing to disclose the fraud. Keywords: Accountability, Civil Servant, Good governance, Transparency, Whistleblowing.